The work values of Portuguese Generation Z in the higher education-to-work transition phase - Silva, Joaquim (2021)
The cohort of young people born with or after the Internet has been dubbed Generation Z (Gen Z, or post-millennials). They are now entering the higher education-to-work transition phase, although this is yet to be studied. Previous studies have found that work values and work preferences vary across generations and national cultures, justifying regular and localised examination. However, very little is known to date about the work values of Portuguese Gen Zs. In this study, we describe the work values of Portuguese university students in the higher education-to-work transition phase and examine their influence on salient work-related preferences. We surveyed over 3000 students attending university degrees from eight main Portuguese universities. We find that Portuguese Gen Zs value social values above all, followed by intrinsic and then extrinsic work values, potentially configuring a unique profile. Work values partially explain work preferences such as employer size and salary expectations. Gender differences mark our results, with women expressing higher work values in all three dimensions and lower entry salary expectations. These results can be useful for employers seeking to attract the best university graduates, facilitate their integration and promote their development.